Literal translation as communication strategy in non-native Japanese language learner's written text - Tajuddin, Farah; Mamat, Roslina (2015)
Learning a foreign language opens up doors of opportunity to the language user. In this study, Japanese language (JL) learners had limited time to learn the language before entering the Japanese university. Being students, having the ability to perform in oral and written communication is important for their academic requirement. However, with limited JL knowledge, it is often that learners encounter difficulties when trying to deliver their intended message. In such situation, learners employ steps known as Communication Strategies (CS) to solve those language problems. In a previous study conducted, the JL learners perceived to depend heavily on their L1 in overcoming language difficulties. However their actual writing did not display their perception. Strategies related to L1 were minimally employed with literal translation (LT) strategy to be the least. Ten high proficiency (HP) learners and ten low proficiency (LP) learners performed a writing activity on spontaneous basis with the writer. The written text was examined to identify CS using Dornyei & Scott’s (1997) inventory of CS. The current study gave focus on their use of LT strategy by highlighting the types of LT employed. The findings revealed that the difference in proficiency level among the two groups exerted difference in the types of LT employed. HP learners translated mostly Malay phrases with cultural content whereas LP learners translated the Malay grammar more. Additionally, the use of LT resulted in both positive and negative outcome in delivering the learners’ message, thus highlighting the need to include cultural information of the society in language learning.